The model of University Entrepreneurial with a systematic approach. (Case Study: University of Mohaghegh Ardabili) - mohammad bashokouh; zahra pooramini (پژوهش در نظام‌های آموزشی, 2022)
The crisis of unemployment as a scourge severely affects all economic, cultural and social aspects of a society and sometimes has irreversible effects, now day, Researchers and government regard entrepreneurship as a solution to unemployment problems. The universities can play an important role in creating new knowledge and entering these competitions and in developing entrepreneurship, especially among the educated people. Therefore, according to the role and importance of entrepreneurship in universities, this study introduces the model of University Entrepreneurial with a systematic approach.This qualitative research uses a content analysis in order to identify patterned meanings across our dataset. To extract the dimensions and components of the University Entrepreneurial system, 15 people were selected using snowball sampling. The ideal criteria of the University Entrepreneurial system are divided into 7 main themes, 29 subsidiary themes, and 110 concepts. The results showed that a University Entrepreneurial system consists of 3 characteristics: input, process and output applying systematic approach in universities, while enhancing industry-university interactions, it will help to create cluster companies, patents, and academic innovations and will increase the number of academic publications and articles.